Skill level and forearm muscle fatigue effects on ball speed in tennis serve - Wang, L.-H.; Lo, K.-C.; Su, F.-C. (Sports Biomechanics, 2021)
This study determined the effect of skill level (ITN 3 vs. ITN 8) on the tennis serve biomechanics and analysed the impact of forearm fatigue on dominant arm mechanisms between the two groups (expert vs. non-expert tennis players). The motion capture system with 17 reflective markers attached on anatomic landmarks of the participant was used for data collection. A total of 12 expert and 11 non-expert tennis players performed the required serving tasks. The ball speed of the expert group was significantly faster than that of the non-expert group during non-fatigued and fatigued states (p < 0.001). The wrist radial/ulnar deviation angle at impact was significantly different between non-fatigued and fatigued states for top-spin (p = 0.030) and flat serves (p = 0.018). A significant increase in extensor carpi ulnaris (ECU) and extensor carpi radialis (ECR) muscle activity during extension (p < 0.010) was observed, with that of the ECU being an ulnar deviation. Both the ECU and ECR might contribute to wrist joint and racket handle stability for the coming acceleration and impact while fatigue occurs. Fatigue might substantially influence non-experts` dominant forearms because of the significantly different elbow joint angles and dominant arm syndromes they displayed as compared with the experts.